Motion predictions of ships in actual operating conditions using potential flow based solver - Rahaman, Md. Mashiur; Islam, H.; Akimoto, H.; Islam, M. R. (Journal of Naval Architecture and Marine Engineering, 2017)
Prediction of ship's response in real voyage condition is essential for efficient ship design. At sea, ships rarely voyage in head wave conditions, and mostly prefer oblique waves for lower resistance and better propulsion. This paper provides oblique wave simulation results for a container, tanker and bulk carrier using a commercial potential flow (PF) based solver, HydroSTAR. Although, PF codes have limitation regarding resistance prediction, they are well reliable in predicting ship motion in waves. The paper aims at providing a relative comparison of ship resistance and motion in different heading angles for three major ship models namely KCS, KVLCC2 and JBC. The paper should prove useful to shippers in case of weather routing or route selection for voyage.